MANAGERIAL OWNERSHIP AS MODERATING VARIABLES IN EFFECT OF PROFITABILITY ON FIRM VALUE - Aprih Santoso; Teguh Ariefiantoro (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study was to examine how the effects of Return on Assets (ROA) on The Firm Value (PBV) with Managerial Ownership (MO) as a moderating variable. The sampling used in this study are firm belonging to the Jakarta Islamic Index (JII) with criteria are: (1) The Company is consistently included in the JII for the period 2016-2017 during the estimated period and window period. (2) Available financial reports published on www.idx.co.id. Based on these criteria, 60 companies are listed in the Jakarta Islamic Index (JII). The results of this study variable Return on Assets (ROA) significant positive effect on the Firm Value (PBV). Variable Managerial Ownership (MO) significantly strengthen the positive relationship between Return on Assets (ROA) with Firm Value (PBV).